Occupational exposure to inorganic particles during pregnancy and birth outcomes: a nationwide cohort study in Sweden. Issue 2 (27th February 2019) - Norlén, Filip; Gustavsson, Per; Wiebert, Pernilla; Rylander, Lars; Albin, Maria; Westgren, Magnus; Plato, Nils; Selander, Jenny
Abstract : Objectives: The aim of this study was to investigate if occupational exposure to inorganic particles or welding fumes during pregnancy is associated with negative birth outcomes. Design: A prospective national cohort study. Setting: All single births from 1994 to 2012 in Sweden. Information on birth weight, preterm birth, small for gestational age, smoking habits, nationality, age, occupation, absence from work and education was obtained from nationwide registers. Exposure to inorganic particles (mg/m 3 ) was assessed from a job exposure matrix. Participants: This study included all single births by occupationally active mothers (995 843). Outcome measures: Associations between occupational exposures and negative birth outcomes in the form of low birth weight, preterm birth and small for gestational age. Results: Mothers who had high exposure to inorganic particles and had less than 50 days (median) of absence from work during pregnancy showed an increased risk of preterm birth (OR 1.18; 95% CI 1.07 to 1.30), low birth weight (OR 1.32; 95% CI 1.18 to 1.48) as well as small for gestational age (OR 1.20; 95% CI 1.04 to 1.39). The increased risks were driven by exposure to iron particles. No increased risks were found in association with exposure to stone and concrete particles. High exposure to welding fumes was associated with an increased risk of low birth weight (OR 1.22; 95% CI 1.02 to 1.45) and preterm birth (OR 1.24; 95% CI 1.07 to 1.42). Conclusions: The results indicate that pregnant women should not be exposed to high levels of iron particles or welding fumes.